2019
DOI: 10.1101/648477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shortened TDP43 isoforms upregulated by neuronal hyperactivity drive TDP43 pathology in ALS

Abstract: Cortical hyperexcitability and mislocalization of the RNA-binding protein TDP43 are highlyconserved features in amyotrophic lateral sclerosis (ALS). Nevertheless, the relationship between these phenomena remains poorly defined. Here, we showed that hyperexcitability recapitulates TDP43 pathology by upregulating shortened (s) TDP43 splice isoforms. These truncated isoforms accumulated in the cytoplasm and formed insoluble inclusions that sequestered full-length TDP43 via preserved N-terminal interactions. Consi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 142 publications
0
15
0
Order By: Relevance
“…At the same time, mislocalised TDP‐43 influences the expression of thousands of genes, so it is also plausible that mislocalised TDP‐43 could influence both excitatory synapses and intrinsic excitability independently and simultaneously (Amlie‐Wolf et al., 2015; Sephton et al., 2011). To add to the complexity of TDP‐43 induced altered excitability in ALS, a recent study elegantly showed that driving hyperexcitability pharmacologically can cause the mislocalisation of TDP‐43 in human‐induced pluripotent stem cell‐derived motor neurons (Weskamp et al., 2020). This indicates that not only can TDP‐43 mislocalisation cause hyperexcitability, but this in turn may drive more TDP‐43 into the cytoplasm in a positive feedback cycle.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, mislocalised TDP‐43 influences the expression of thousands of genes, so it is also plausible that mislocalised TDP‐43 could influence both excitatory synapses and intrinsic excitability independently and simultaneously (Amlie‐Wolf et al., 2015; Sephton et al., 2011). To add to the complexity of TDP‐43 induced altered excitability in ALS, a recent study elegantly showed that driving hyperexcitability pharmacologically can cause the mislocalisation of TDP‐43 in human‐induced pluripotent stem cell‐derived motor neurons (Weskamp et al., 2020). This indicates that not only can TDP‐43 mislocalisation cause hyperexcitability, but this in turn may drive more TDP‐43 into the cytoplasm in a positive feedback cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hyperexcitability was found to lead to the expression of two shortened splice isoforms of TDP-43 (sTDP-43-1 and sTDP-43-2), wherein the entire glycine-rich domain of TDP-43 is replaced by short tails generated by the inclusion of a new exon encoding a unique 18-amino acid C-terminus not found in the wild-type full-length TDP-43 (Fig. 2) [111]. The sTDP-43-1 isoform is prone to cytoplasmic localization due to a de novo NES created by the neural activity-dependent splicing.…”
Section: Neural Activity-dependent Alternative Splicing Of Tdp-43mentioning
confidence: 99%
“…Cortical hyperexcitability is a highly conserved feature of both sporadic and familial ALS patients (Bae, Simon, Menon, Vucic, & Kiernan, 2013; van den Bos, Geevasinga, Higashihara, Menon, & Vucic, 2019; Geevasinga et al., 2015; Menon et al., 2017), which precedes symptom onset and muscle weakness, and is a strong predictor of disease progression, negatively correlating with the Amyotrophic Lateral Sclerosis Functional Rating Scale‐Revised Score (Geevasinga, Menon, Ozdinler, Kiernan, & Vucic, 2016; Menon, Kiernan, & Vucic, 2015; Shibuya et al., 2016; Van den Bos, Menon, et al, 2018). As an important pathophysiological process in ALS, a recent study has shown that hyperexcitability can also drive the emergence of TDP‐43 pathology in vulnerable motor neurons (Weskamp et al., 2020). TDP‐43 is the major pathological protein in ALS.…”
Section: Npy’s Impact On Pathogenic Als Mechanismsmentioning
confidence: 99%